Exact periodic wave solutions of a singular integrable equation - Xie, Shaolong; Gao, Bin (Mathematical Modelling and Analysis, 2011)
In this paper, theory of dynamical systems is employed to investigate periodic waves of a singular integrable equation. These periodic waves contain smooth periodic waves, periodic cusp waves and periodic cusp loop waves. Under fixed parameter conditions, their exact parametric expressions are given.